Gender And Poverty Among Elderly In Malaysia - Masud, Jariah; Zainalaludin, Zumilah (Archives of Business Research, 2019)
The purpose of this study is (1) to examine gender differences in sources of income and poverty among elderly in Malaysia; and (2) to identify factors influencing poverty among male and female elderly in Malaysia. Data for this study were obtained from Malaysian Household Income Survey in 2009 conducted by The Department of Statistics Malaysia. A Total of 16,325 elderly involved in the study. Analysis of descriptive, chi-square and logistic regression were used to address the objectives. Results reveals that gender differences were found in sources of income and poverty among elderly. The main sources of income for both elderly men and women were transfer income. However, majority of men also received income from earning while majority women did not received any money. Higher proportion of women compared to men were poor. Women did not have sources of income which can buffer from poverty. Results from logistic regression explained that, elderly men who are younger and not having sources of income (paid employment, earned, property and transfer) were more likelihood being poor compared to their counterpart. Meanwhile, women who are older, living in rural area, homemaker and not having sources of income (paid employment, earned, property and transfer) were more likelihood being poor compared to their counterpart. It can be concluded that sources of income and age are factors that help both men and women elderly out from poverty. This study might become an additional sources for researcher due to limited study on poverty which focus on gender especially in Malaysia.